Upaya Pelestarian Kecapi Tradisional Melalui Implementasi Pembelajaran Kecapi Pada Sekolah Dasar di Amparita Kabupaten Sidrap - Andi Ihsan (Publikasi Pendidikan, 2022)
This study aims to describe descriptively the learning of traditional harp in elementary schools in Amparita sub-district, Sidrap district. This research is a descriptive research with a qualitative approach. Data was collected through observation, interviews, and documentation which were then analyzed by reducing the data, displaying and further verifying the data. The results of the study indicate that there are various strategies used in preserving traditional lutes through learning in elementary schools, namely learning gradually at different grade levels both theory and practice, using harps with sizes that are adjusted to the physical size of students, and the involvement of harp artists in the learning process at school. school.